Complex support of technological development of environmentally friendly toilet systems in passenger trains - S. P. Kiseleva; O. V. Kanunnikov; G. A. Arakelova; P. V. Zozulya (Управление)
Ensuring environmental-oriented turnover of fecal waste in passenger transport is necessary for the preservation of ecosystems, public health and sustainable development of transport complexes. The history of Russian railway toilet complexes begins with the launch of the first railway “Petersburg – Tsarskoe Selo” in 1837. In the USSR since 1985 The Ministry of Railways of the USSR thought about the need for experimental design work on the creation of closed systems for collecting sewage for passenger rolling stock. A set of scientific works on the creation of systems and equipment that protect the environment from chemical and  biological pollution was presented in the Railway transport program for 1990-2000.The article considers the negative impact of fecal waste on the environment and public health, as well as problems related to the maintenance of environmentally friendly toilet complexes of passenger cars. The main results of technological development of toilet complexes of transport systems have been outlined. The authors note the importance of timely comprehensive support (infrastructure, technical, organizational and economic, regulatory and methodological, personnel, and other) for the technological development of toilet complexes in the transport industry. In particular, the article reviewes some of the current problems of infrastructure, regulatory and methodological, organizational and economic support for the operation and maintenance of environmentally friendly toilet complexes. For the effective functioning of the environmentally friendly toilet complexes system of transport systems, the authors propose to use organizational and methodological tools that will allow you to systematically determine the actual level of technological development of the fecal waste disposal system of the environmentally friendly toilet complexes of passenger trains, to develop directions and measures to improve its  environmental and economic efficiency.